2021
DOI: 10.15557/jou.2021.0017
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound shear wave elastography of the anterior talofibular and calcaneofibular ligaments in healthy subjects

Abstract: Aim of study: Most sprained lateral ankle ligaments heal uneventfully, but in some cases the ligament’s elastic function is not restored, leading to chronic ankle instability. Ultrasound shear wave elastography can be used to quantify the elasticity of musculoskeletal soft tissues; it may serve as a test of ankle ligament function during healing to potentially help differentiate normal from ineffective healing. The purpose of this study was to determine baseline shear wave velocity values for the lateral ankle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition, many new US methods have been derived clinically. Ultrasonic shear wave elastography found that the shear wave velocity of normal lateral ankle ligament increased with the increase of applied force[ 30 ]. Non-invasive virtual touch tissue imaging quantification, a novel ultrasonic palpation method, can identify the hardness difference of acute type I ATFL injuries and evaluate ligament elasticity.…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…In addition, many new US methods have been derived clinically. Ultrasonic shear wave elastography found that the shear wave velocity of normal lateral ankle ligament increased with the increase of applied force[ 30 ]. Non-invasive virtual touch tissue imaging quantification, a novel ultrasonic palpation method, can identify the hardness difference of acute type I ATFL injuries and evaluate ligament elasticity.…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…Color coded elastograms can identify the "stiffness" of a structure. Gimber et al 31 established normative data for ankle ligament stiffness that can potentially be used in the clinical setting for the evaluation of healing.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Further, it can potentially produce false negatives for ligament lesions, which would occur if the ligament was subjected to a yo-yo effect [ 11 , 13 , 15 , 16 , 17 , 18 ]. While staying at rest, it would exhibit a normal morphological structure, but leads to increased fiber elasticity, caused by a bad local collagen quality or quantity [ 19 ]. The prediction on the dynamic behavior of the ligament is possible even in a static exam such as MRI since this exam generates a good definition of the ultrastructure of tissues [ 1 , 17 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%